Certification — Right to Certification for a Sectarian Organization Restricted to Members of the Christian Faith — Right Denied - MacLean, L.A. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1962)
SummarySection 10 of the Ontario labour Relations Act, concerning certification of unions, as well as Section 4 of The Fair Employment Practices Act require that a trade union must extend the opportunity of membership and the right incidental to membership, equally and impartially and on the same terms and conditions to persons of all creeds. Any arbitrary or discriminatory denial of these right and opportunities is not only inimical to basic democratic principles but is incompatible wtih the union's obligation as an exclusive bargaining agent to represent all employees in the bargaining unit.Trenton Construction Workers Association, local No 52, affiliated with the Christian Labour Association of Canada, Applicant, and Tange Company Limited, Respondent; Ontario Labour Relations Board, File No. 20576-60, November 13, 1961. L.A. MacLean, Deputy Vice-Chairman, and Board Members G. Russel Harvey and R.W. Teagle.